Aktivitas Anticendawan dan Antibakteri Minyak Atsiri Ekstrak Kulit Buah Jeruk Purut terhadap Patogen Penting Tanaman Jeruk - Triasih, Unun; Ikarini, Imro’ah; Widyaningsih, Sri; Wicaksono, Rudi Cahyo (Jurnal Fitopatologi Indonesia, 2023)
Antifungal and Antibacterial Activity of Essential Oils of Kaffir Citrus Fruit Peel Extract Against Important Pathogens of Citrus PlantsMain diseases of citrus plants caused by fungi and bacteria can inhibit plant growth, resulting in a decrease in plant production. Disease controls implemented so far mostly relied on synthetic chemical pesticides which have the potential to have negative impacts on the environment and health. Essential oil from the peel of kaffir lime (Citrus hystric) contains compounds that have the potential to inhibit the growth of pathogens in citrus plants. The aim of this research was to determine the antifungal and antibacterial activity of kaffir lime peel essential oil at five concentrations i.e., 0.5%, 1%, 2%, 3%, and 5% against citrus plant pathogens, namely Colletotrichum gloeosporioides, Fusarium oxysporum, and Xanthomonas axonopodis. The results showed that all essential oil concentrations tested had a low category of inhibitory activity against F. oxysporum, and a medium inhibitory activity against C. gloeosporioides. As on X. axonopodis the essential oil showed strong inhibitory activity at concentrations 3% and 5%. Kaffir lime peel essential oil has the potential as antifungal and antibacterial in citrus plants and can be used as an alternative control technology that is environmentally friendly and safe.